Synthesis, Molecular Docking, MEP and SAR Analysis, ADME-Tox Predictions, and Antimicrobial Evaluation of Novel Mono- and Tetra-Alkylated Pyrazole and Triazole Ligands - Y. Kaddouri; B. Bouchal; F. Abrigach; M. El Kodadi; M. Bellaoui; R. Touzani (Journal of Chemistry)
Newly synthesized compounds of N-alkylated heterocyclic compounds were prepared by condensation of amine with alcohol which undergoes a reaction of SN2. These newly synthesized derivatives were characterized by spectral analysis. The objective is to prepare new potent nontoxic antimicrobial agents which are easy to synthesize and could be scaled up in pharmaceutical industries. Thirteen new heterocyclic compounds containing a pyrazole moiety were synthesized with good yields (29.79 to 99.6%) and were characterized by FTIR, 1H NMR, 13C NMR, and CG-MS techniques. The compounds were divided into two series—monoalkylated compounds (1–11) and tetra-alkylated compounds (12 and 13)—and then evaluated for their in vitro antifungal and antibacterial activities against several fungal and bacterial strains. None of the monoalkylated compounds had antibacterial or antifungal activity. However, the two tetra-alkylated pyrazole ligands displayed strong antibacterial potential. Moreover, compound 12 was more potent against all tested bacterial strains than compound 13. Interestingly, compounds 12 and 13 acted as weak antifungal agents against Saccharomyces cerevisiae. ADME-Tox studies suggested that compounds 12 and 13 exhibit better toxicity profiles than the commercial antibiotic streptomycin. MEP studies suggested that compounds 12 and 13 have the same charge locations but differ in their values which are due to the condensed geometry of compound 13 that make it more polarizable than compound 12. Of particular interest, these different MEPs were evident in ligand protein docking, suggesting that compound 12 has better affinity with MGL enzyme than compound 13. All these findings suggested that these novel compounds represent promising antibacterial lead compounds.